2021
DOI: 10.3390/app112311568
|View full text |Cite
|
Sign up to set email alerts
|

Methodology of 3D Scanning of Intangible Cultural Heritage—The Example of Lazgi Dance

Abstract: Traditional dance is one of the key elements of Intangible Culture Heritage (ICH). Many scientific papers concern analysis of dance sequences, classification and recognition of movements, making ICH data public, creating and visualising 3D models or software solutions for learning folklore dances. These works make it possible to preserve this disappearing art. The aim of this article is to propose a methodology for scanning folklore dances. The methodology was developed on the basis of capturing 3D data via an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…From the perspective of protection, the main research methods are as follows: (1) Digital technology is to be used to systematically record skills and the experience of the inheritors combined with modern storage technologies such as databases, data management, and data retrieval to establish a complete and orderly database with standardized management [13][14][15][16], and (2) image recognition technology and 3D modeling are to be used to restore and record the operation process of ICH skills and crafts making [17][18][19][20].…”
Section: Related Work 21 Study On Digitization Of Ichmentioning
confidence: 99%
“…From the perspective of protection, the main research methods are as follows: (1) Digital technology is to be used to systematically record skills and the experience of the inheritors combined with modern storage technologies such as databases, data management, and data retrieval to establish a complete and orderly database with standardized management [13][14][15][16], and (2) image recognition technology and 3D modeling are to be used to restore and record the operation process of ICH skills and crafts making [17][18][19][20].…”
Section: Related Work 21 Study On Digitization Of Ichmentioning
confidence: 99%
“…They reported that there were very few examples of Intangible heritage recorded through motion capture [21,22] and all of them were dedicated to recording dance. Other studies use Motion Capture to analyse dance elements [23][24][25][26][27] but few -if any-use the technology to capture musical instrument playing.…”
Section: Inventoryingmentioning
confidence: 99%
“…The widest group of articles [2][3][4][5][6][7] are concerned with the 3D information technology techniques and methods that are used to protect and popularize the cultural heritage. Another group of papers [8][9][10][11] examine the practical aspects of using information technology to popularize cultural heritage and detect vandalism in the form of graffiti.…”
Section: Three-dimensional Information Technologies In Cultural Heritagementioning
confidence: 99%
“…Skublewska et al present an innovative method of digitally capturing of folk dances [6]. They use a motion-capture technique and installation, as well as a developed wire model of the human hand, which complements the whole-body model.…”
Section: Three-dimensional Information Technologies In Cultural Heritagementioning
confidence: 99%